FDZ data description: "Survey on marginally employed workers and their employers (MinijobsNRW)" - Lukas Hörnig; Sandra Schaffner (RWI - Leibniz-Institut für Wirtschaftsforschung, 2020)
Marginal employment, so-called Minijobs, represent a significant part of the dependent employment in Germany. In 20121 and 2016 the RWI conducted a survey and interviewed marginally employed workers and employers with marginally employed workers in North Rhine-Westphalia. The results of the survey allow to draw conclusions for the structure of the employees, the motivations of the employees and the employers and the perception of rights like the continued payment of wages and maternity leave. The data is available for academic research as a Scientific-Use-File from the FDZ Ruhr at RWI.
Keywords: J21; J30; J81; J83; L20; C30; 330; marginal employment; Germany; survey data; minimum wage